Developing a virtual geriatric perioperative medicine clinic: a mixed methods healthcare improvement study. (15th May 2021) - Joughin, Andrea; Ibitoye, Sarah; Crees, Amy; Shipway, David; Braude, Philip
Abstract: Background: the Geriatric Perioperative Care clinic at North Bristol NHS Trust was suspended in March 2020 during the COVID-19 pandemic. A virtual clinic was piloted to deliver preoperative health optimisation and shared decision-making for patients undergoing critical elective surgery. No literature existed on virtual preoperative clinics for older people to support the development. Objective: this healthcare improvement study describes the setup and delivery of the virtual clinic as its primary aim. Secondary aims included: assessing older people's access to technology and their digital literacy for virtual consultation; to describe barriers and facilitators for consultations, as well as evaluation of patient and clinician satisfaction with the consultations' mode of delivery and outcomes. Methods: a mixed methods healthcare improvement study was undertaken through plan-do-study-act cycles, semi-structure interviews, and quantitative service benchmarking. Results: the pilot evaluated 67 preoperative consultations (43.3% video, 56.7% telephone, mean age 75) with a mix of surgical pathology (vascular 88.1%, colorectal 10.4%, urological 1.5%). Patient feedback demonstrated improved understanding of conditions (90.6%), and adequate opportunity to express opinions and questions (96.2%). Clinicians preferred video consultations (adequate to deliver services: 89.7% video; 68.4% telephone). The greatest barriers to engagement, none of which were exclusions to participation, included cognitive impairment, sensory impairment, or needing technical assistance setting up video consultations (52.2%). Conclusions: delivering a virtual preoperative medical optimisation and shared decision clinic for older people is feasible. This study will aid other units in developing their own virtual preoperative clinics. Future work should evaluate perioperative outcomes of delivering a face-to-face versus virtual clinic.